Boys as writers: perspectives on the learning and teaching of writing in three primary schools. (7th June 2017) - Edwards, Gillian; Jones, Jane
Abstract: Boys' attitude to writing is widely perceived as an issue in English primary and secondary schools. Prior research has identified a link between negative attitudes to writing and lower achievement and raised the issue of the stereotyping of boys as underachievers in literacy. The study reported here suggests that if we are to understand the problems associated with the underachievement of boys, we should take into account boys' perspectives on their experiences as literacy learners. In this study, boys aged 8–11 drawn from three London schools in the UK, were interviewed in small groups annually over 3 years of their primary schooling. The boys' teachers were also interviewed separately. These interviews generated insights into the teachers' views of the boys and the boys' views of themselves as literacy learners, especially as writers. The data indicated the boys were highly sensitive to the social situation in the classroom. The boys responded best to their literacy learning when their teachers treated them as individuals, valued their ideas and incorporated strategies for developing learner agency into their daily classroom practice. This article concludes that a teaching approach that includes consulting children about what helps or hinders their learning and a fresh teacher focus on gender issues would increase gender awareness.